2017
DOI: 10.1186/s12974-017-0838-1
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory signature of cerebellar neurodegeneration during neonatal hyperbilirubinemia in Ugt1 -/- mouse model

Abstract: BackgroundSevere hyperbilirubinemia is toxic during central nervous system development. Prolonged and uncontrolled high levels of unconjugated bilirubin lead to bilirubin-induced neurological damage and eventually death by kernicterus. Bilirubin neurotoxicity is characterized by a wide array of neurological deficits, including irreversible abnormalities in motor, sensitive and cognitive functions, due to bilirubin accumulation in the brain. Despite the abundant literature documenting the in vitro and in vivo t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 71 publications
(107 reference statements)
2
40
0
1
Order By: Relevance
“…Additionally, IL-1β induced a fast increase in extracellular glutamate contents, which affected the excitotoxicity of cells exposed to glutamate, leading to neural damage [ 48 ]. However, the pro-inflammatory cytokines activated by the MAPK signaling pathway and NF-κB signaling pathway via binding to IL-1 receptor 1 recruit more cytokines and immune cells, resulting in deleterious cell injury [ 5 , 6 , 20 , 34 , 35 ]. In the present study, IL-1β and IL-18 expression increased in UCB-treated astrocytes, whereas VX-765 could prevent this inflammatory cascade and inhibit the activation of caspase-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, IL-1β induced a fast increase in extracellular glutamate contents, which affected the excitotoxicity of cells exposed to glutamate, leading to neural damage [ 48 ]. However, the pro-inflammatory cytokines activated by the MAPK signaling pathway and NF-κB signaling pathway via binding to IL-1 receptor 1 recruit more cytokines and immune cells, resulting in deleterious cell injury [ 5 , 6 , 20 , 34 , 35 ]. In the present study, IL-1β and IL-18 expression increased in UCB-treated astrocytes, whereas VX-765 could prevent this inflammatory cascade and inhibit the activation of caspase-1.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that elevated levels of UCB activated astrocytes and microglia, as well as gliosis, with a subsequent upregulation of inflammatory markers, such as tumor necrosis factor alpha (TNF-α), interleukin (IL)-1β, and IL-6 [ 15 18 ]. In turn, the increased cytokines could further exacerbate nerve cell death and inflammatory responses by activating the MAPK and nuclear factor-kappaB (NF-κB) signaling cascades [ 17 , 19 , 20 ]. Interestingly, blocking pro-inflammatory cytokine production decreased UCB-induced cell death, either by the loss of membrane integrity or by apoptosis [ 7 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…qRT-PCR experiments were performed as previously described (Bockor et al, 2017;Vodret et al, 2017). Briefly, total RNA from mouse livers was prepared using EuroGOLD Trifast (Euroclone, Milano, Italy).…”
Section: Mrna Quantification Analysis (Qrt-pcr)mentioning
confidence: 99%
“…Here we have developed a new animal model of bilirubin toxicity and investigated the consequences of this toxicity in the auditory brainstem, which is associated with hearing loss. The most commonly used animal model of hyperbilirubinaemia is the Gunn rat and Ugt1 -/- mice [ 24 , 47 , 48 ]. Gunn rats having been administered sulfadimethoxine (to displace endogenous bound bilirubin from albumin) have been used to investigate bilirubin toxicity [ 6 , 21 , 23 ].…”
Section: Discussionmentioning
confidence: 99%